1999
DOI: 10.1152/jappl.1999.86.3.924
|View full text |Cite
|
Sign up to set email alerts
|

Hindlimb immobilization applied to 21-day-oldmdx mice prevents the occurrence of muscle degeneration

Abstract: Dystrophin-deficient skeletal muscles of mdx mice undergo their first rounds of degeneration-regeneration at the age of 14-28 days. This feature is thought to result from an increase in motor activity at weaning. In this study, we hypothesize that if the muscle is prevented from contracting, it will avoid the degenerative changes that normally occur. For this purpose, we developed a procedure of mechanical hindlimb immobilization in 3-wk-old mice to restrain soleus (Sol) and extensor digitorum longus (EDL) mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
36
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 32 publications
6
36
0
2
Order By: Relevance
“…On the other hand, it is important to keep in mind that a single therapeutic exercise can influence different muscles of the same limb in different manners. In agreement with the results presented by Kimura et al (2006) that immobility can lead to preservation of dystrophic muscle in humans DMD Mokhtarian et al (1999) investigated whether immobilization of the hindlimbs of the mdx-mice would prevent the occurrence of muscle degeneration. The authors clarify that dystrophin-deficient skeletal muscle of mdx-mice undergo their first rounds of degeneration-regeneration at the age of 14-28 days.…”
Section: Pt Exercise Prescriptionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, it is important to keep in mind that a single therapeutic exercise can influence different muscles of the same limb in different manners. In agreement with the results presented by Kimura et al (2006) that immobility can lead to preservation of dystrophic muscle in humans DMD Mokhtarian et al (1999) investigated whether immobilization of the hindlimbs of the mdx-mice would prevent the occurrence of muscle degeneration. The authors clarify that dystrophin-deficient skeletal muscle of mdx-mice undergo their first rounds of degeneration-regeneration at the age of 14-28 days.…”
Section: Pt Exercise Prescriptionsupporting
confidence: 89%
“…Regenerated myofibers was attested by the presence of central nuclei in dystrophic fibers. According to these authors (Mokhtarian et al 1999), limb immobilization prevents the occurrence of the first round of myofibers necrosis in mdx-mice and reinforces the idea that muscle contractions play a role in the skeletal muscle degeneration of dystrophin-deficient muscles. Even though some authors have suggested that restriction of movement prevent cycles of degeneration and regeneration in dystrophic muscle, we should consider that restriction of movement leads to muscle disuse and has drastic consequences to the patients, e.g.…”
Section: Pt Exercise Prescriptionsupporting
confidence: 61%
“…Similarly, limb immobilization or treatment with muscle relaxants prevent and reduce the occurrence of muscle degeneration in mdx mice (Mokhtarian et al, 1999). One possible explanation for this observation is that reduced movement and force production allows for the cell to repair damage at dense bodies and plasma membrane.…”
Section: The Function Of Dys-1 In Dense Body and Sarcolemma Integritymentioning
confidence: 99%
“…Initially, before the animal becomes mobile the muscle fibers are normal in appearance, although the plasma creating kinase is elevated. There are several studies on the mdx mouse which show that if muscles are immobilised either by denervation or mechanically using rods or a cast, dystrophic changes do not occur in the muscle (see for example; Mokhtarian et al, 1999). So the absence of dystrophin is thought to either weaken the membrane and/or alter the activity of membrane ion channels.…”
Section: Dystrophinopatheis a 2 Stage Pathology: The Importance Of Brmentioning
confidence: 99%